Karakterisasi Tes Kemampuan Pemecahan Masalah Siswa Pada Materi Tekanan Zat Berdasarkan Analisis Teori Respon Butir - Nofifah Ayu; Winny Liliawati; Harun Imansyah (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
Problem solving skills are one of the skills that a student really needs to survive in the 21st century. In order to have problem solving skills, of course a child must be taught and accustomed to practicing them from an early age starting from school. This research aims to determine the characteristics of the test instruments used to measure students' problem solving abilities based on item response theory analysis. This research uses a mix method with a sequential exploratory research design. This research used instruments that had been prepared by researchers which were then validated by experts and then tested on 130 students who had studied material on pressure in substances. The data obtained were analyzed using item response theory analysis, the GRM model (Graded Response Model). This research shows that the instrument prepared by the researcher is suitable for measuring students' problem solving abilities by having a validity value (0.89) and a b value or difficulty level in the range -2 to 2 which means good and can be used.